Multi-year Prediction of Rice Yield under the Changing Climatic Scenarios in Nepal Central Terai Using DSSAT Crop Model - Amgain, Lal Prasad; Adhikari, Sailesh; Pandit , Samiksha (Journal of Nepal Agricultural Research Council, 2022)
NASA-POWER derived weather data of Dumkauli in Nawalparasi (27.68˚ N, 84.13˚E) district in the Nepal central Terai for the past 33-years (1984/85-2017/18) were purposively downloaded and validated with recorded weather data of Department of Hydrology and Meteorology (DHM). The trend analysis for grain yield of rice in Nawalparasi was drawn with the historical data of the maximum and minimum temperatures and rainfall. Positive correlations between grain yields and minimum temperature and rainfall each showed an acceptable coefficient of determination (R2). The CSM-CERES-Rice embedded in DSSAT ver 4.7 was used for multi-year prediction of rice yield using both historically recorded and simulated climatic scenarios. The model simulated results closely agreed with the observed rice yield recorded by the Ministry of Agriculture and Livestock Development (MoALD) in Nepal. The correlation between precipitation and observed rice yield was 0.71 and the correlation between precipitation and observed and DSSAT simulated yield was 0.379. The multi-year predicted rice yield using historical weather data and the DSSAT rice model showed that rice yield could be sustained with the use of the current crop cultivars only for the upcoming few years. The climate index, mainly the rainfall index, was found to be more sensitive to rice production in the Nepal central Terai region. This study suggests for the development of new climate change ready rice cultivars to feed the increasingly growing Nepalese population.